2019
DOI: 10.1155/2019/8215017
|View full text |Cite
|
Sign up to set email alerts
|

Neuroplasticity and Neuroprotective Effect of Treadmill Training in the Chronic Mouse Model of Parkinson’s Disease

Abstract: Physical training confers protection to dopaminergic neurons in rodent models of parkinsonism produced by neurotoxins. The sparing effect of physical training on dopaminergic neurons can be tested with training applied during chronic MPTP treatment, while the neurorestorative effect when training is applied after completing such treatment. In this study, the effect of the onset of training respective to chronic MPTP treatment was specifically addressed. Three groups of mice were injected with 10 doses of MPTP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 72 publications
(92 reference statements)
3
24
0
Order By: Relevance
“…Even though a single exercise causes a BDNF increase in the blood of patients with PD, it is short-lived and is not associated with an improvement in the neurological status of the patients. Studies using an animal model of parkinsonism have provided evidence that only the repetition of medium-or high-intensity physical exercise for several weeks or a continuous training process causes an increase in BDNF [179] and TrkB receptor levels [131,180] in the brain regions responsible for motor activity in rats.…”
Section: Possible Mechanisms Underlying the Protective Effect Of Bndfmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though a single exercise causes a BDNF increase in the blood of patients with PD, it is short-lived and is not associated with an improvement in the neurological status of the patients. Studies using an animal model of parkinsonism have provided evidence that only the repetition of medium-or high-intensity physical exercise for several weeks or a continuous training process causes an increase in BDNF [179] and TrkB receptor levels [131,180] in the brain regions responsible for motor activity in rats.…”
Section: Possible Mechanisms Underlying the Protective Effect Of Bndfmentioning
confidence: 99%
“…Under the influence of the training process, increased BDNF expression in the hippocampus, cerebral cortex, ST, brainstem, and spinal cord was observed [131,174,179,181,182]. Animal studies have shown that long-term endurance training increased both TrkB receptor and TH expression in structures involved in extrapyramidal movement regulation, i.e., in the ST and midbrain [128,129,179,[183][184][185].…”
Section: Possible Mechanisms Underlying the Protective Effect Of Bndfmentioning
confidence: 99%
See 1 more Smart Citation
“…This protocol is moderate-to high-intensity exercise based on the definition of moderate treadmill exercise in mice [74][75][76]. They reported that in both early and late-onset exercise (treadmill) training, there was (a) preservation of dopaminergic neurons in substantia nigra pars compacta (SNpc) and ventral tegmental area (VTA), (b) an increase in brain-derived neurotrophic factor in the midbrain and glial cell line-derived neurotrophic factor in the striatum, and (c) mitigation of the pro-inflammatory response in the SNpc and VTA [73].…”
Section: Role Of Exercise In Neuroprotectionmentioning
confidence: 99%
“…In human models, it has been shown that sustained moderate exercise can improve QoL in PD and is likely to help to down-regulate neuroinflammation [12,72,78,[80][81][82][83][84][85][86][87][88][89][90][91]. Going from moderate-to high-intensity exercise (in animal models) further reduces neuroinflammation, which implies neuroprotection [73,77]. O'Callaghan et al showed that high-intensity interval training (HIIT) exercise significantly increased the neuroprotective substance brain-derived neurotrophic factor (BDNF) compared to both moderate-intensity exercise and controls [92].…”
Section: Role Of Exercise In Neuroprotectionmentioning
confidence: 99%